Газоанализаторы на основе пористого карбида кремния - Moskovchenko, N. N.; Svetlichny, A. M. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
Various designs of gas analyzers based on porous silicon carbide are presented. The potential of using this material as the active layer of sensors is demonstrated.